Aggression vs. psychic resilience system - on an example of male judo. The case study - Małgorzata Pujszo; Robert Stępniak; Natalia Jasińska (Kazimierz Wielki University, 2019)
A lot of researches concerning martial arts area showed psychological links, what suggests to others researchers that they should follow and penetrate that path [1,2]. Aggression is one of the inborn human features. It is helpful in fight for survival. Scientists defined many kinds of aggression that are interconnected with each other. The basic division recognizes: instrumental aggression and hostile aggression. Instrumental aggression is when it is not intended to harm someone but to provoke a certain behavior, e.g. winning a combat. Hostile aggression on the other hand is when it is intended to harm someone [3]. So it can be said that there is a division on acceptable aggression, which can be even useful, and the one that leads to not following any rules under the influence of emotions- unacceptable aggression. Aggression can be observed in every aspect of human life (home, school, sport life). So it is reasonable to ask if sport, which is dominated by acceptable aggression (instrumental), where unacceptable aggression is immediately punished, can be a restraint of unacceptable aggressive behaviors [4]. Researches by Dąbrowski and others showed that most of judo athletes display valuable, social and moral attitude. It can be said that training that sport discipline by socially maladjusted individual can help them to find the right way [5]. Another researches in that area by Pietrzak and Cynarski showed that according to Bushidō Code, martial art it is not only the training of the body but also of the 'spirit 'of the warrior. Followers can enrich their characters, spirits and ability to assess and solve situations [6]. Each man has different ability to react to other people aggressive behaviors. It depends on their psychic resilience, to be precise their psychic flexibility. Psychic resilience in sport is determined as a kind of psychic disposition necessary for the athlete to achieve success in competition [7,8,9]. The term psychic resilience can be defined as a dynamic occurrence of ability of adaptation in given situations [10]. In this context, it can be said that psychic resilience has stabilizing action and means a lower inclination to disturbances, which is seen in good psychic condition [11]. Mutual interactions of both dimensions of human psychic- aggression and psychic resilience, together with sport training seem to be an interesting researching problem.